Relevansi nilai-nilai budi pekerti pada novel mata dan rahasia pulau gapi dengan pembelajaran PKn kelas VI sekolah dasar - Rifai, Adji Muhammad Nur; Sukarno, Sukarno; Yulisetiani, Septi (Universitas Sebelas Maret, 2022)
The purpose of this study is to find out about the values of character in the novel. and its relevance to Civics learning for Class VI Elementary School which can be used as an investment for students. The obligation to cultivate character in students is contained in the Minister of Education and Culture Number 23 of 2015. The character values contained in the novel are useful as learning media in order to foster character values in students through Civics subjects. The research method used is a qualitative approach. The source of the data used in this research is the novel Mata and Secret of Gapi Island. Data collection techniques used are content analysis and interview techniques. The data analysis technique in this study is an interactive analysis model, namely data reduction, data presentation, and drawing conclusions. The validity test uses theoretical triangulation and source triangulation. The results of the study obtained that there are 11 values in the novel Mata and Secret of Gapi Island, namely religious, disciplined, honest, hard working, creative, independent, curious, cares about the environment, friendly/communicative, likes to read, and loves peace. The highest score in the novel Mata and Secret of Gapi Island is the value of curiosity with six findings. Values that are relevant to the learning materials for grade VI SD are peace-loving values, religious values, friendly/communicative values, hard work values, environmental care values, and discipline values. The values of character that are relevant to the learning materials for class VI SD can be used as an alternative to character building by making the findings a medium for learning texts.